INCORPORATION OF H(3)-THYMIDINE INTO CHLOROPLAST DNA OF MARINE ALGAE - Steffensen, Dale M. (The Rockefeller University Press, 1965)
The chloroplasts of three genera of marine algae, Dictyota, Padina, and Bryopsis, were labeled with tritiated-thymidine for various time periods during culture in "Erd-Schreiber's" solution. Autoradiographs were prepared from both smeared and sectioned material. They revealed that almost all of the radioactivity was in the cytoplasm and associated with the chloroplasts, as detected in the overlying silver halide crystals. Deoxyribonuclease, ribonuclease, and hot trichloracetic acid treatments indicated that the loss of radioactivity corresponded to the removal of DNA and not RNA. Quantitative studies of silver grain distribution suggested that the radioactivity of the labeled DNA originated from the edge of the pyrenoids on either side in the longitudinal direction of Bryopsis chloroplasts. Nuclei did not incorporate H(3)-thymidine even though cells were dividing rapidly in the three genera examined. It is postulated that the enzyme, thymidine kinase, is absent as a coding sequence of nuclear DNA in algae, but is present in chloroplast DNA. When the chloroplasts of Dictyota and Padina in various stages of division were scored for labeling, there appeared to be a DNA synthesis period, analogous to S period in cell division. This chloroplast-labeling period occurred just previous to fission. Many of the criteria seem to have been satisfied to establish the self-reproducing and semi-autonomous nature of chloroplasts, especially when combined with the chemical, genetic, and morphological evidence.